The Role of Islamic Culture in Improving Hospital Employee Performance in Indonesia - Dwi Putranto, Ega; Aini, Qurratul (Universitas Aisyah Pringsewu, 2024)
Islamic leadership is based on the traits of the Prophet Muhammad and is the single most important factor in achieving higher productivity in the workplace. Incorporating Islamic principles into the workplace can boost employee happiness and productivity. The method used in the preparation is a literature review. Secondary data, collected from other research projects, is what this study is based on. The research results show that efficient employee performance is very important and mandatory in Islam, especially in the health industry. This section explores Islamic principles that are closely related to improving employee performance, including piety, honesty, accountability, patience, cooperation, fairness, consultation, and self-criticism. The conclusion of this research is that Islamic culture/values in improving the performance of hospital employees are sabr, ta'awun, al-'adl, shura, muhasabah an-nafs, tauhid, justice, freedom, responsibility, and ihsan.